Silver decorated lithium niobat nanostructure by UV activation method for silver–lithium niobate/silicon heterojunction device - Evan T. Salim; Wafaa K. Khalef; Makram A. Fakhri; Rawan B. Fadhil; Ahmad S. Azzahrani; Raed Khalid Ibrahim; Raid A. Ismail (Scientific Reports, 2023)
Abstract Lithium niobite (LiNbO3) nanostructure were successfully synthesized by chemical bath deposition method (CBD) and then decorated with silver nitrate (AgNO3) through UV activation method at different immersion durations (5, 15, 25, 35, and 45 s). The silver nanoparticles (AgNPs) effects on the optical and structural properties were studied and analyzed using various scientific devices and technique. X-ray diffraction (XRD) results showed that all the samples have a hexagonal structure with a maximum diffraction peak at the (012), and the existence of silver atoms could be recognized at 2θ = 38.2° which corresponds to the (111) diffraction plane. The optical absorption of nanocomposites depicted the presence of plasma peak related to silver (Ag) at 350 nm. The estimated energy gap from the optical absorption revealed a reduction in the Eg value from (3.97 eV) to (3.59 eV) with the presence of Ag atom. The Photolumincence (PL) peaks were observed at around 355 nm for pure LiNbO3/Si and 358, 360, 363, 371, 476 nm for different immersion durations respectively, in the visible region of the electromagnetic spectrum. The scanning electron microscopy (SEM) study illustrated that with increasing the immersion time, especially at 45 s, a change in the particle morphology was observed (LiNbO3 NRs structure). Atomic force microscopy (AFM) displayed that the surface roughness decreases from 80.71 nm for pure sample to 23.02 nm for the decorated sample as the immersion time is increased. FT-IR manifested a noticeable increase in the intensity of the peaks of samples decorated with AgNPs. Raman spectroscopy elucidated that the peaks shifted to higher intensity due to the plasmonic effect of Ag nanoparticles. Ag–LiNbO3/Si heterojunction nano-devices were fabricated successfully and enhanced the optoelectronic properties in comparison with the pure LiNbO3/Si heterojunction device.